Ion association in lithium metaborate solution: a Raman and ab initio insight. (4th March 2017) - Zhu, Fayan; Zhou, Yongquan; Fang, Chunhui; Fang, Yan; Ge, Haiwen; Liu, Hongyan
ABSTRACT: Ion association and hydration clusters in aqueous lithium borate solution are extremely important to understand some extraordinary properties of lithium borates. In the present work, polyborate distribution in aqueous LiBO2 solution was investigated through Raman and thermodynamics equilibrium analysis. Geometry and stability of hydrated clusters LiB(OH)4 (H2 O) n up to n = 8 were calculated at the B3LYP/aug-cc-pVDZ level. Three different types of ion association, namely, contact ion pairs (CIP), solvent-shared ion pairs (SIP) and solvent separated ion pairs (SSIP) were obtained; characteristics of all of these stable configurations were determined, and the most stable hydrated clusters were chosen. Then the mechanisms of ion aggregation and crystal nuclei formation in the LiB(OH)4 solution were proposed. The tight four-hydrated sphere of Li + makes it difficult for the dehydrated form of its first hydration sphere to from a CIP, which is the passible reason that lithium borate always has a large super-saturation degree.